The Rights of the Visually Impaired People in Access to Copyright Protected Works at the International and National Levels : (Comparative Study) - Hussein T. Faidhallah; Mahdi Maghdid Qadr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
he rights of the visually impaired in access to copyright works is one of the most challenging issues at the international and national levels, and is rarely studied before. Also, there is divergence among jurists about it, where some give absolute right to visually impaired people in access to protected works such as books, researches, audio recordings and other types of protected works, even without permission or financial compensation to the author, while others are not with absolute right to access, due to the need of protecting the financial interests of the author and the related rights. This research is a legal attempt to clarify the positions of copyright laws ar national and international levels, aiming at presenting the best pracices to solve the legal problems. The research is divided into two chapters, addressing the rights of the visually impaired in access to protected works in general, and the position of copyright laws in the first chapter, while focused on exclusive rights and flexibilities in copyright provisions in the second chapter. At the end, reached several conclusions, most importantly is that there are different legal positions between the compaired laws, also found that Iraqi and Kurdistan laws have gaps and shortcomings about the subject. We have recommended that Iraq must ratify and join the Marrakesh Treaty of 2013, that will include Kurdistan region as well, and then amend the copyright and related rights laws to adopt the most prominent provisions of the Marrakech Treaty.